O Teorema do Ponto Fixo de Banach e algumas Aplicações - Barros, Cícero Demétrio Vieira de (2013)
In this work we make a study of the theory of the metric spaces in order to present the Banach Fixed Point Theorem? and then, it is applied in the solution of some nonlinear equations with an iterative method for obtaining a solution. After that, three applications of the Banach Fixed Point Theorem are presented. The rst one is the Theorem of the Existence and Uniqueness of Solutions of Ordinary Di erential Equations. The second one has as theme the application of the Banach Fixed Point Theorem in the area of compression images on the Internet. In the third application, it is presented how the Google searcher works and what is the cause of its success.